Analysis of the Polyák Imre & Varga János memorial Ranking Series Tournament Budapest 2025 - implications for rules - Dokmanac, M. (International Journal of Wrestling Science, 2025)
This analysis compares the application of new rules at the European Senior Championship (Bratislava, April 2025) and the IV Ranking Series Tournament (Budapest, July 2025). In both events, under GR style, if a match ended 1-1, the wrestler who scored first was declared the winner. The International Rules of Wrestling for these two events remain unchanged. Judges awarded 1 point for the first and second passivity; after the third, only the active wrestler could choose to continue in parterre or standing position, with no additional points given. For this analysis, three European Championships from 2022 to 2024 were reviewed, all using the rule that in a 1-1 tie, the wrestler who scored last wins: